Frequency of Post Spinal Hypotension in Elective Cesarean Section after Spinal Anesthesia - Javed Iqbal, Shahid Mabood, Syed Sana Ullah, Riyan Qasim, Afaq Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The aim purpose of this research was to raise awareness about the prevalence of hypotension and to increase anaesthetists’ vigilance about possible measures to reduce the risk factors of hypotension after spinal anaesthesia in emergency patients undergoing caesarean section at the Hayatabad Medical Complex Peshawar. Study design: The cross sectional study was conducted at the Hayatabad Medical Complex Hospital Peshawar. Place and Duration: A concurrent observational study conducted at Hayatabad Medical Complex Peshawar with permission and approval from the Medical Superintendent. The study was conducted from July 2022 to December 2022. Method: This prospective study was conducted on 272 patients, in which the patients underwent elective CS under SA. The data collection has been indicated in the patient record, then the following information is filled in the data collection sheet: Gander age, MR number, blood pressure before spinal anesthesia, blood pressure after spinal anesthesia, use of antihypertensive drugs, the patient under spinal anesthesia was according to the standard protocol of HMC Hospital Peshawar, data will be collected from participants willing to participate in the study, then patient data will be collected through direct observation and the interview. Result: we collect data from 272 patients which were treated from spinal anesthesia for caesarian section 73 participants (26.8%) had post-operative hypotension. Different age weight and different drug doses were used in spinal anesthesia, 18-29 years 16 patients (21.9%) and 30-40 years 57 patients (78.1%) were experienced with hypotension. Conclusion: Based on patient weight, a total of 272 participants weighing between 49-65 kg 9 patients (12.3%), whereas in 66-80 kg 21 patients (28.8%), and 81-90 kg had 43 patients (58.9%) were suffered from hypotension. Keywords: Cesarean section, spinal anesthesia, spinal induce hypotension,